Morphometric Analysis of Placental Terminal Villi, Capillaries, and Intervillous Space in Normal and Pre-Eclamptic Pregnancies - Abdullah Khilji, Syed Faizan Ali Rizvi, Samina Tarique, Sabahat Fatima, Azhar Ali Shah, Qamber Haider Kazmi, Tabinda Urooj (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The placenta reflects the prenatal problems that are linked to high perinatal morbidity and mortality both macroscopically and microscopically. A pregnancy syndrome called pre-eclampsia has terrible consequences for both the mother and the unborn child. It may result in more frequent inductions of labor, fetal growth limitation, respiratory issues in newborns, increased admission rates to neonatal critical care units, and an elevated risk of perinatal or fetal death. To understand the relation of preeclampsia and fetal growth identification of its effects on various components of the placenta is mandatory hence the current study was designed to evaluate the Placental Terminal Villi, Capillaries, and Intervillous Space in Normal and Pre-eclamptic Pregnancies. Methodology: It was a cross sectional study, carried out on 50 samples of placentas, out of which 25 were preeclamptic and 25 were normal. The placentas were recruited after cesarean session, processed as per guidelines and were analyzed for histopathological examination. The set inclusion criteria were Registered cases of Pre-eclampsia, Blood Pressure ≥ 140/90 mmHg, Parity 0 – 4, Age of mother (25 – 35) Years., Gestational Age (36 – 42) Weeks, Mode of delivery Cesarean Sections. The set exclusion criteria were known hypertensive patients, and patient diagnosed with other chronic illnesses. Results: Number of terminal villi, Transverse diameter of terminal villi (μm), Intervillous space (μm), and Transverse diameter of terminal villous capillaries decreased significantly (p=0.001) in preeclamptic group however, Number of terminal villous Capillaries were found to be increased in preeclamptic group (p=0.001). Conclusion: Preeclampsia leads to more significant alterations in placental structure compared to normal pregnancies, emphasizing the importance of early detection and management of this condition to improve maternal and fetal outcomes. Keywords: Pregnancy, preeclampsia, terminal villi, Intervillous space, terminal villous Capillaries